8th AIAA Theoretical Fluid Mechanics Conference 2017
DOI: 10.2514/6.2017-3481
|View full text |Cite
|
Sign up to set email alerts
|

Combining A Reduced Polynomial Chaos Expansion Approach with Universal Kriging for Uncertainty Quantification

Abstract: Engineering design optimization studies, based on the large number of computational fluid dynamics simulations necessary for uncertainty quantification, are computationally expensive. Polynomial chaos expansion methods have the potential to save computational costs by reducing the number of input design parameters. Kriging methods are able to accurately predict off-design values and give an estimate of their error. However, each has its limitations. In this paper, we combine a reduced dimensional polynomial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In our previous work, 1 we found that the RPC-K metamodel provides more accurate estimates for nonsmooth flows than the RPC metamodel. However, a few solutions indicated discontinuities and/or underpredicted values.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In our previous work, 1 we found that the RPC-K metamodel provides more accurate estimates for nonsmooth flows than the RPC metamodel. However, a few solutions indicated discontinuities and/or underpredicted values.…”
Section: Introductionmentioning
confidence: 83%
“…We evaluated the model in the present study on an engine nacelle inlet design case from our previous works. 1,4 This case shows the performance of the metamodel on a realistic CFD simulation with non-smooth flow behavior. The CFD simulations were solved using the CFD++ solver from Metacomp Technologies.…”
Section: Iva Problem Setupmentioning
confidence: 90%
See 3 more Smart Citations